2019
DOI: 10.1177/1365480219835323
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of social inequality and poverty on the mental health and wellbeing and attainment of children and young people in Scotland

Abstract: The poverty-related attainment gap is an internationally recognised problem. There is growing recognition that it cannot either be understood or addressed without taking cognisance of children’s mental health and wellbeing. The focus of this conceptual article is to examine the impact of social inequality and poverty on the mental health and wellbeing and attainment of children and young people in Scotland through the lens of resilience. While not a ‘state of the art’ literature review, a systematic approach w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Second, financially disadvantaged individuals might have longer working hours, which prevent them from socially interacting with others. Moreover, poorer financial status might be a risk factor for social isolation (Samuel, Alkire, Zavaleta, Mills, & Hammock, 2018) and poorer health and mental health (Mowat, 2019), which in return result in higher levels of loneliness (Hawkley & Kocherginsky, 2018). Surprisingly, to date, there has been only limited research to look at the relationship between subjective social status and loneliness (Rubin et al, 2016).…”
Section: Subjective Social Status and Lonelinessmentioning
confidence: 99%
“…Second, financially disadvantaged individuals might have longer working hours, which prevent them from socially interacting with others. Moreover, poorer financial status might be a risk factor for social isolation (Samuel, Alkire, Zavaleta, Mills, & Hammock, 2018) and poorer health and mental health (Mowat, 2019), which in return result in higher levels of loneliness (Hawkley & Kocherginsky, 2018). Surprisingly, to date, there has been only limited research to look at the relationship between subjective social status and loneliness (Rubin et al, 2016).…”
Section: Subjective Social Status and Lonelinessmentioning
confidence: 99%
“…Similarly, Okoroji et al [62] showed that stigmatization processes produced by representations in media and politics make poor people suffer from marginalization, which in turn causes vulnerability for psychological distress. Another study demonstrates that social injustice and poverty increases negative child experiences [82]. Some other studies focus on poverty in third-world countries which point to similar negative psychological outcomes (see also [83,84]).…”
Section: Outcomes Of Povertymentioning
confidence: 85%
“…For a further eight focal children attainment and wellbeing diverges in the move from nursery to Primary 1 and for the remaining four wellbeing and attainment converge: coming closer together over time. In many ways such alignments are the more expected outcome: the literature suggests a relationships between positive wellbeing, engagement and attainment (Upadyaya and Salmela-Aro, 2013;Cadime et al, 2016;Mowat, 2019) and conversely a drop in engagement and wellbeing may herald a drop in attainment. The extent to which this sample of children reflects the peer group, variability is to be expected in attainment and wellbeing at times of transition.…”
Section: Aligning Wellbeing and Attainment Over Timementioning
confidence: 99%